Experimental Studies of Concrete-Filled Composite Tubes under Axial Short- and Long-Term Loads - Marcin Abramski (Materials, 2020)
The paper presents experimental studies on axially compressed columns made of concrete-filled glass fiber reinforced polymer (GFRP) tubes. The infill concrete was C30/37 according to Eurocode 2. The investigated composite pipes were characterized by different angles of fiber winding in relation to the longitudinal axis of the element: 20, 55 and 85 degrees. Columns of two lengths, 0.4 m and 2.0 m, were studied. The internal diameter and wall thickness of all the pipes were identical and amounted to 200 mm and 6 mm, respectively. The mean values of two mechanical properties, elasticity modulus and compression strength, were determined. These properties were determined for longitudinal compression and for circumferential tension. The graphs of longitudinal and peripheral deformations of polymer shells as a function of load level are presented both for empty tubes and for concrete-filled ones. The results of long-term investigations of three identically made 0.4 m high concrete-filled GFRP tubes are also presented.